Comparisons of cirrus cloud microphysical properties between polluted and pristine air - Diao, Minghui; Schumann, Ulrich; Minikin, Andreas; Jensen, Jorgen (2015)
In this work, we analyze high-resolution (~200 m), in-situ observations from two global flight campaigns: 1) the HIAPER Pole-to-Pole Observations (HIPPO) global campaign in 2009-2011 funded by the US National Science Foundation (NSF), and 2) the Interhemispheric Differences In Cirrus Properties from Anthropogenic Emissions (INCA) campaign in 2000 funded by the European Union and participating research institutions. The HIPPO campaign observations were obtained over the North America continent and the central Pacific Ocean from 87ºN to 67ºS. During the INCA campaign, cirrus clouds were sampled with optical particle counters in the size range of about 1 to 800 m at midlatitudes, mainly over the Pacific west of Punta Arenas and over the North Atlantic west of Great Britain. We find that as CO concentration increases, the cirrus clouds tend to have smaller ice crystals (HIPPO data based on Fast-2DC ice probe > 87.5 µm), higher Nc of small particles (INCA data based on ice crystals > 3 µm measured by FSSP instrument), and slightly lower Nc for larger particles (HIPPO data Fast-2DC > 87.5 µm and INCA 2DC data for particles > 100 µm). These three features are consistent with each other, indicating that when there is stronger signature of anthropogenic emission, ice crystals would be more numerous and smaller.